What is the best modality for diagnosing pancreatic cancer?. Issue 4 (22nd March 2022) - Fujimori, Nao; Minoda, Yosuke; Ogawa, Yoshihiro
Abstract : This Editorial refers to the article by S. Omoto et al., p 198‐206 of this issue DEN 34:1 .